Factors Associated with Low Back Pain (LBP) Complaints among Computer-Using Office Workers at Sri Pamela Hospital, Tebing Tinggi City, in 2025 - Wahyuni, Sri; Achmad Rifai; Basyariah Lubis (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Objective: This study aims to analyze the factors associated with low back pain (LBP) complaints among computer-using office workers at Sri Pamela Hospital, Tebing Tinggi City, in 2025.Method: This research employed a quantitative approach with a cross-sectional design. The sample included all computer-using office workers at Sri Pamela Hospital. Data were collected using a questionnaire covering individual characteristics such as age, length of service, body mass index, smoking habits, physical activity, and working duration, as well as complaints of LBP. Data were analyzed using bivariate and multivariate methods. Results: The study found that age, length of service, body mass index, smoking habits, physical activity, and working duration were significantly associated with LBP complaints. Additionally, workplace ergonomics and sitting posture also contributed to the occurrence of LBP.Conclusion: LBP complaints among computer-using office workers are influenced by various individual and workplace factors. Preventive efforts should focus on improving ergonomics, increasing physical activity, and promoting healthy lifestyle management in the workplace.